Effects of a Very Low-Carbohydrate High-Fat Diet and High-Intensity Interval Training on Visceral Fat Deposition and Cardiorespiratory Fitness in Overfat Individuals: A Randomized Controlled Clinical Trial - Cipryan, Lukas; Dostal, Tomas; Litschmannova, Martina; Hofmann, Peter; Maffetone, Philip B.; Laursen, Paul B. (Frontiers in Nutrition, 2021)
Purpose: This randomized controlled parallel-group study examined the effects of a very low-carbohydrate high-fat (VLCHF) diet and high-intensity interval training (HIIT) program over 12-weeks on visceral adipose tissue (VAT) and cardiorespiratory fitness (CRF) level in overfat individuals. Methods: Ninety-one participants were randomly allocated to the HIIT (N=22), VLCHF (N=25), VLCHF+HIIT (N=25), or control (N=19) groups for 12 weeks. Body composition and CRF were analyzed before the experimental period and after 4, 8, and 12 weeks. Dual-energy X-ray absorptiometry (DXA) and graded exercise test (GXT) to volitional exhaustion were used for the body composition and CRF assessments, respectively. Results: There were significant between-group differences in the VAT mass and body composition outcome changes. VAT mass decreased after 12 weeks only in the VLCHF and VLCHF+HIIT groups (p < 0.001, median [95% CI]: VLCHF: -142.0 [-187.0; -109.5] g; VLCHF+HIIT: -104.0 [-135.0; -71.0] g). Similarly, changes in body mass, total body fat, trunk fat mass, waist and hip circumferences were distinctly decreased in the VLCHF and VLCHF+HIIT groups, when compared to HIIT and Control groups. Total lean mass significantly decreased in the VLCHF and VLCHF+HIIT groups (-2.1 [-3.0; -1.6] kg and -2.5 [-3.6; -1.8] kg, respectively) after 12 weeks. While the HIIT program significantly increased total time to exhaustion in the GXT, peak oxygen uptake was unchanged. Conclusions: A VLCHF diet, either in isolation or in combination with HIIT, was shown to induce a significant reduction in VAT mass and body composition variables. HIIT alone did not cause such effects on body composition, but improved exercise capacity. The VLCHF diet groups displayed no detrimental effects on high-intensity exercise performance. The Our findings indicate that the VLCHF diet and exercise training provoked different and isolated effects on body composition and CRF.